2015
DOI: 10.1016/j.colsurfa.2014.10.062
|View full text |Cite
|
Sign up to set email alerts
|

Membrane interaction of a new synthetic antimicrobial lipopeptide sp-85 with broad spectrum activity

Abstract: ARTICLE IN PRESS• Sp-85 is a new synthetic antibiotic lipopeptide with broad spectrum activity.• Pressure-area curves of mixed monolayers show non-ideal mixing.• Binding to anionic liposomes results in fusion and leakage of aqueous contents.• TEM images of antibiotic-exposed bacteria show damaged membranes.• A mechanism of action based on bacterial membrane destabilization is proposed.g r a p h i c a l a b s t r a c t a r t i c l e i n f o a b s t r a c tAntimicrobial peptides offer a new class of therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…The only Dab residue involved in lactam cyclization was substituted with another natural amino acid, Lys. Indeed, previous study confirmed the importance of the presence of two Arg residues in favoring electrostatic interactions of polymyxin [9,10]. On the other hand, several works from our lab studied the synthesis of Lys analogues of different types of polymyxins [13,14].…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…The only Dab residue involved in lactam cyclization was substituted with another natural amino acid, Lys. Indeed, previous study confirmed the importance of the presence of two Arg residues in favoring electrostatic interactions of polymyxin [9,10]. On the other hand, several works from our lab studied the synthesis of Lys analogues of different types of polymyxins [13,14].…”
Section: Resultssupporting
confidence: 59%
“…For instance, the replacement of the 6-methylheptanoic fatty acid in Polymyxin B with aromatic Fmoc molecule resulted in analogues with high antibacterial activity and significant reduced toxicity [8]. Another study confirmed the importance of the presence of two Arg residues in favoring electrostatic interactions of polymyxin [9,10]. An interesting work showed that adding the sequence formyl-Met-Leu-Phe to the linear tripeptide tail (L-Dab 1 -L-Thr 2 -L-Dab 3 ) conferred chemotactic and opsonic activities upon the conjugates, which were 8 to 10 times less toxic than the parent polymyxin antibiotic [11].…”
Section: A M Hamza 1 a A Kalmouch 1* Sa El-mowafi 1 A Mmentioning
confidence: 93%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first report showing that lipopeptides inhibited the growth of P. putida. Grau-Campistany et al (2015) provided strong evidence that lipopeptides altered the bacterial membrane permeability barrier. Furthermore, Greber et al (2019) reported that lipopeptides showed a significant effect on cell membrane permeability.…”
Section: Discussionmentioning
confidence: 97%
“…Histidine metabolism is also found to be involved in biofilm formation and is confirmed by gene disruption (Cabral et al, 2011). Histidine kinase is an important signaling molecule in biofilm formation in gram-positive and negative bacteria (McLoon et al, 2011;Shemesh and Chai, 2013;Grau et al, 2015). In addition, several ABC transporter system proteins were significantly up-regulated in the tylosin inhibiting biofilm formation.…”
Section: Discussionmentioning
confidence: 99%